Biological evaluation of some octanoyl derivatives of methyl 4,6-O-cyclohexylidene-α-D-glucopyranoside - Kabir, Abul KMS; Kawsar, Sarkar MA; Bhuiyan, Mohammad MR; Rahman, Md Safiqur; Banu, Bilkiss (Chittagong University Journal of Biological Sciences, 2013)
Some acylated derivatives of methyl 4,6-O-cyclohexylidene-?-D-glucopyranoside, including the precursor, were employed as test compounds for in vitro antimicrobial functionality test against ten human pathogenic bacteria and six phytopathogenic fungi. For comparative studies, biological activity of standard antibiotics, Ampicillin and Nystatin were also carried out against these microorganisms. The study revealed that the tested samples exhibited moderate to good antibacterial and antifungal activities. It was also observed that the test substances were more effective against fungal phytopathogens than those of the bacterial strains. Encouragingly, a good number of test compounds exhibited better antimicrobial activity than the standard antibiotics employed. Minimum Inhibition Concentration (MIC) test of methyl 4,6-O-cyclohexylidene-3-Odecanoyl- 2-O-octanoyl-?-D-glucopyranoside was conducted against INABA ET (Vibrio) and MIC was found to be 12.5 ?g/disc. DOI: http://dx.doi.org/10.3329/cujbs.v3i1.13406 The Chittagong Univ. J. B. Sci.,Vol. 3(1&2):53-64, 2008